2016
DOI: 10.1111/jtxs.12177
|View full text |Cite
|
Sign up to set email alerts
|

Texture Quality of Candied Fruits as Influenced by Osmotic Dehydration Agents

Abstract: Candied fruits produced with healthier ingredients for obtaining low glycemic index, low energy and/or dietary fiber enriched products were develop by substituting the traditionally used osmotic dehydration sugars sucrose and glucose by fructose, sorbitol, maltitol, fructooligosaccharides and galactooligosaccharides. Quality of candied fruits was evaluated chemically, rheologically and sensorially. For all fruits the final composition was dependent on the osmotic dehydration agent used and, in all cases, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…This increase could be related to the distribution of sugar content in the sample tissue—more specifically, the adherence of sucrose content on the surface of samples, leading at the same time to the increase in firmness. The authors in [ 7 ] studied candied fruits (pineapple, orange-peel, citron) developed by substituting the sucrose and glucose with fructose, sorbitol, maltitol, fructooligosaccharides (FOS) and galactooligosaccharides (GOS). They concluded that each osmotic solute significantly affected the texture of the candied fruits, but these changes were dependent on the fruits.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This increase could be related to the distribution of sugar content in the sample tissue—more specifically, the adherence of sucrose content on the surface of samples, leading at the same time to the increase in firmness. The authors in [ 7 ] studied candied fruits (pineapple, orange-peel, citron) developed by substituting the sucrose and glucose with fructose, sorbitol, maltitol, fructooligosaccharides (FOS) and galactooligosaccharides (GOS). They concluded that each osmotic solute significantly affected the texture of the candied fruits, but these changes were dependent on the fruits.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that there was no significant difference in total acceptability scores for the different alternative sweeteners applied, leading to a preliminary promising finding that sucrose could be effectively replaced in the traditional tomato candying process. It has been reported that the most important sensory characteristics affecting the consumer acceptance of OD-processed candied fruits are the flavor/taste and texture characteristics depending on the osmotic solute used, as well as the raw material (fruit) [ 7 , 68 ]. From a commercial point of view, it would be necessary to implement a wide consumer’s trial to assess the palatability and acceptance of the different osmodehydrated products.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…En esta fractura macroscópica, los tejidos de la pitahaya pueden fallar por ruptura de la pared celular y por la pérdida de unión o adherencia entre células generada por alteración de las lamelas que es una capa compuesta de polisacáridos que rodea la pectina de la pared celular y genera la unión entre las células [12]. Este comportamiento es característico de frutas enteras y mínimamente procesadas y se ha observado en la compresión uniaxial de diferentes productos cortados y enteros como calabaza fresca y deshidratada osmóticamente [12] manzana y papa [31], piña [32] y frutas confitadas [33].…”
Section: Propiedades Mecánicasunclassified